A novel investigation method for axonal damage in neuromyelitis optica spectrum disorder: In vivo corneal confocal microscopy. Issue 1 (March 2021) - Altıntaş, Ayşe; Yildiz-Tas, Ayse; Yilmaz, Sezen; Bayraktutar, Betul N; Comert, Melis Cansu; Zimmermann, Hanna; Brandt, Alexander U; Paul, Friedemann; Sahin, Afsun
Background: Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory autoimmune disorder that damages optic nerves, brainstem, and spinal cord. In vivo corneal confocal microscopy (IVCM) is a noninvasive technique that provides corneal images with dendritic cells (DCs) and corneal subbasal nerve plexus (SBP), which arises from the trigeminal nerve. Objective: We investigated corneal SBP changes in NMOSD and proposed IVCM as a potential new disease severity biomarker for NMOSD. Methods: Seventeen age-sex matched NMOSD patients and 19 healthy participants underwent complete neurologic and ophthalmologic examinations. The duration of disease, first symptom, presence of optic neuritis attack, antibody status, Expanded Disability Status Scale(EDSS) score and disease severity score(DSS) were recorded. Retinal nerve fibre layer (RNFL) thickness was measured with optical coherence tomography, and corneal SBP images were taken with IVCM. Results: NMOSD patients had significantly reduced corneal nerve fibre lenght-density and corneal nerve branch lenght-density compared with controls, while DC density was increased. NMOSD patients also showed significantly reduced RNFL thickness compared with controls. EDSS, DSS levels were inversely correlated with IVCM parameters. Conclusion: We observed significant corneal nerve fibre loss in NMOSD patients in relation to disease severity. IVCM can be a candidate noninvasive imaging method for axonal damage assessment in NMOSD that warrants further investigation.